2020
DOI: 10.3758/s13414-020-02185-x
|View full text |Cite
|
Sign up to set email alerts
|

Reading proficiency predicts the extent of the right, but not left, perceptual span in older readers

Abstract: Given that increased word skipping is a key index of age-related changes in reading (Paterson et al., 2020), we conducted a supplementary analysis of the total number of words skipped during older adults' first-pass reading of the sentences. This analysis showed a significant effect of sentence difficulty because older readers skipped more words in easy versus hard sentences (b =-0.07, SE = 0.03, t =-2.73). There were also significant effects of both right window contrasts (3-vs. 9-letter: b = 0.41, SE = 0.03,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In contrast, Rayner et al (2009) observed that older adults showed no additional benefit from window sizes larger than one word to the right of fixation, and were more disrupted than younger readers by being deprived of one word to the left. Veldre et al (2021) recently confirmed the increased leftward extent of the perceptual span among older readers and showed that the size of the rightward span depended on written language proficiency. These findings suggest that older readers have a smaller and less asymmetric perceptual span than younger readers.…”
Section: Parafoveal Processing In Readingmentioning
confidence: 72%
“…In contrast, Rayner et al (2009) observed that older adults showed no additional benefit from window sizes larger than one word to the right of fixation, and were more disrupted than younger readers by being deprived of one word to the left. Veldre et al (2021) recently confirmed the increased leftward extent of the perceptual span among older readers and showed that the size of the rightward span depended on written language proficiency. These findings suggest that older readers have a smaller and less asymmetric perceptual span than younger readers.…”
Section: Parafoveal Processing In Readingmentioning
confidence: 72%
“…The major eye-movement signatures claimed to index this strategy were slower reading times owing to longer fixations and more regressions (attributed to slower lexical processing), and increased skipping, longer forward saccades, and enhanced word frequency and predictability effects (which were attributed to a compensatory increased reliance on prediction to "guess" upcoming words; Rayner et al, 2006). Although the risky reading hypothesis has motivated further research (e.g., Paterson et al, 2020) and computational modeling (McGowan & Reichle, 2018; see also Laubrock et al, 2006), questions have been raised about the strength and consistency of the evidence underpinning it (Payne & Silcox, 2019;Veldre et al, 2021Veldre et al, , 2022.…”
Section: Cognitive Aging and Predictabilitymentioning
confidence: 99%
“…The participants were seated 55 cm from the camera while their heads were fixed using a chin rest. Only the right eye movements were tracked [35]. Natural reading performance was measured: the participants silently read 30 different sentences from the child's version of the Russian sentence corpus [36,37].…”
Section: Apparatus and Stimulimentioning
confidence: 99%